Virtual Screening and Comparison of the Binding Effectiveness of Doxorubicin, Paclitaxel, and Ergoloid to ERβ-MDM2 Complex Protein as New Breast Cancer Drug Candidates - Salmasfattah, Novyananda; Dhiani, Binar Asrining; Muslikh, Faisal Akhmal; Putra, Galih Satrio (http://dharmais.co.id/, 2025)
Background: The prevalence of breast cancer continues to increase, it is the second leading cause of death after lung cancer. Estrogen receptor beta (ERβ) has an important role in breast cancer pathology, activation of Akt pathway will trigger E3 ubiquitin ligase murine double minute 2 (MDM2) to ERβ, which will increase the risk of breast cancer. Thus, both proteins have potential as therapeutic agents in breast cancer drug development. This study aims to find breast cancer drug candidates from natural products and compare the effectiveness of these compounds with Doxorubicin and Paclitaxel.Method: ERβ (PDB ID: 3OLS) and MDM2 (PDB ID: 1T4E) proteins were combined using ClusPro 2.0. Doxorubicin and Paclitaxel ligands were obtained from PubChem, there are 842 natural products obtained from the ZINC database, when the energy minimization is reduced to 839 natural products. Virtual screening between proteins and ligands was performed using PyRx 8.0, followed by analysis of amino acid residues resulting from interactions between proteins and ligands using protein interaction calculator (PIC) and protein ligand interaction profiler (PLIP). Results: Ergoloid compounds have the lowest binding affinity compared to doxorubicin and paclitaxel compounds, and are able to interact strongly with the ERβ-MDM2 Protein as determined from the results of interactions between proteins and ligands using PIC and PLIP.Conclusion: Ergoloid compounds can interact well with ERβ-MDM2 Protein. Thus, it can be used as a breast cancer drug candidate in the future. In vitro, in vivo, and biochemical testing needs to be done to confirm this discovery